Upaya Guru Pendidikan Agama Islam dalam Menanamkan Nilai Pluralisme Agama di SMAN 1 Dampit - Ridho Andi Fauzi (SAP (Susunan Artikel Pendidikan), 2023)
This research aims to explore the efforts made by Islamic Religious Education (PAI) teachers in instilling the value of religious pluralism in senior high schools (SMA), especially in Dampit. Religious pluralism is a concept that encourages recognition and respect for diverse religious beliefs and views. In the context of education, understanding and applying the values of religious pluralism can help form a young generation who is tolerant and appreciates religious differences. This study used qualitative research methods by interviewing a number of PAI teachers at a high school. The collected data was analysed using a thematic approach to identify concrete efforts made by PAI teachers to instill the value of religious pluralism. The research results showed that PAI teachers adopt various strategies, such as using a dialogic approach and in-depth understanding of various religions. This research was conducted between January and July 2023 with the aim of providing a deeper understanding of the role of PAI teachers in developing an understanding of religious pluralism among high school students. The implication of this research is that religious education can be an important understanding in promoting inclusive attitudes and mutual understanding in a multicultural and multireligious society.